Temperature features of molecules' dynamics in "heavy water - glycerol" solution - O. A. Vasylkevych; V. I. Slisenko (Ядерна фізика та енергетика)
By the method of quasi-elastic scattering of slow neutrons, the dynamics of molecules of the solution "heavy water - glycerol" with glycerol concentration of 0.046 molar fractions has been studied in the temperature range (2 - 10) °С. The features in the temperature dependence of total self-diffusion coefficient and its one-particle component are found: at 3 °C deep minimum is observed. In this case, the residence time of the molecule of glycerol in the vibrational state increases substantially. The analysis shows that these effects are due to increase in the intensity of the clustering processes at 3 °C.